2021
DOI: 10.1186/s13075-021-02603-x
|View full text |Cite|
|
Sign up to set email alerts
|

The citrullinated/native index of autoantibodies against hnRNP-DL predicts an individual “window of treatment success” in RA patients

Abstract: Background There is a need for biomarker to identify patients “at risk” for rheumatoid arthritis (risk-RA) and to better predict the therapeutic response and in this study we tested the hypothesis that novel native and citrullinated heterogeneous nuclear ribonucleoprotein (hnRNP)-DL autoantibodies could be possible biomarkers. Methods Using protein macroarray and ELISA, epitope recognition against hnRNP-DL was analysed in sera from different develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…MAP4, a microtubule-associated protein expressed in proliferating cells, has been found to participate in in vivo phosphorylation, thereby affecting the cell cycle, cytoskeleton stability (42), and cellular apoptosis (43). HNRNPDL was reported to extensively regulate transcription and alternative splicing, which was veri ed in diseases such as muscular dystrophy (44) and rheumatoid arthritis (45). Moreover, HNPNPDL has also been suggested to prevent cognitive decline induced by aging and Alzheimer's disease by modulating RNA splicing(46).…”
Section: Discussionmentioning
confidence: 99%
“…MAP4, a microtubule-associated protein expressed in proliferating cells, has been found to participate in in vivo phosphorylation, thereby affecting the cell cycle, cytoskeleton stability (42), and cellular apoptosis (43). HNRNPDL was reported to extensively regulate transcription and alternative splicing, which was veri ed in diseases such as muscular dystrophy (44) and rheumatoid arthritis (45). Moreover, HNPNPDL has also been suggested to prevent cognitive decline induced by aging and Alzheimer's disease by modulating RNA splicing(46).…”
Section: Discussionmentioning
confidence: 99%
“…Like RA33, hnRNP DL was also targeted as either native or citrullinated autoantigen in RA patients at dissimilar stages (Marklein et al, 2021). The citrullinated/native index of anti‐hnRNP DL autoantibodies seemed to be of value in identifying individuals at risk for RA and predicting the therapeutic response especially in those seronegative for RF/anti‐CCP2 (Marklein et al, 2021). In addition, 20% of sera from RA patients also reacted with AUF1 (Skriner et al, 2008).…”
Section: Hnrnps Are Autoantigens In Autoimmune Diseases and Associate...mentioning
confidence: 99%
“…The recombinant hnRNP DL expressed in Escherichia coli can be recognized by all tested anti‐Sm autosera obtained from SLE patients, indicating hnRNP DL as a novel autoantigen for SLE (Chang et al, 2013). Both native and citrullinated hnRNP DL were reactive to sera of SLE patients, and citrullination seemingly brought about novel structural epitopes recognized by SLE sera that were negative for cyclic citrullinated peptides (Marklein et al, 2021). Autoantibodies directed to hnRNP D can also be detected in around 33% of SLE patients and four out of five anti‐Sm‐positive sera, and the epitope was mapped to the conformational structure within the N‐terminal RNA‐binding region thought on which the RNA binding activity was unacted (Skriner et al, 2008).…”
Section: Hnrnps Are Autoantigens In Autoimmune Diseases and Associate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors reported an error in Additional file 1 wherein the track changes are visible. The Additional file 1 has been updated.…”
mentioning
confidence: 99%